Perceptions of adjudicated juveniles concerning their parole experience - McClain, Lynette G., author; Lehmann, Jean P., advisor (Colorado State University. Libraries, 2000)
Using a qualitative analysis, this study examined the perceptions of successful and unsuccessful adjudicated youth concerning their parole experience. This study was conducted using a qualitative ethnomethodological approach in order to understand the structure and essence of the adolescent parole experience of four different groups of ex-parolees. This study answered the following four research questions. 1. What are the perceptions of youth concerning experiences before, during and after parole? 2. What are the differences and similarities of youth who were successful in treatment and on parole and those who were unsuccessful in treatment and on parole? 3. What are the experiences of successful and unsuccessful youth before, after and during parole? 4. What experiences do these youth view as critical to their success and failures? A convenience sample of 18-21 year old male parolees from the State of Colorado, Department of Human Services, Division of Youth Corrections program was selected for the study. Participants were categorized as successful or unsuccessful while adjudicated and on parole. Each group was interviewed using an open-ended interview model to determine their perceptions regarding their parole experience. The researcher had served all of the respondents during their parole supervision and included information she gathered over a twelve-month period to as part of the research study. Results were analyzed and compared to existing literature. In summary, based upon the responses for fifteen adjudicated delinquent youth, this study makes the following recommendations: 1. Youth with less interruption in their development are more able to learn from their mistakes and be rehabilitated than those with numerous and multiple interruptions. 2. Parole treatment of youth who have been unsuccessful in residential treatment or on parole needs to be multi-modal and multilevel individualized and long term and must adapt to the changing needs of adolescents. 3. Adolescent youth who are not successful in treatment or on parole have not resolved their own personal identity crisis and are limited in their ability to fully evaluate or describe the perceptions of their experiences.
Keywords: criminology; welfare; perceptions; juvenile justice; parole and probation